2017
DOI: 10.1007/s00330-017-4844-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-based surrogate markers of transcriptome subclasses and signatures in hepatocellular carcinoma: preliminary results

Abstract: Objectives In this preliminary study, we examined whether imaging-based phenotypes are associated with reported predictive gene signatures in hepatocellular carcinoma (HCC). Methods 38 patients (M/F 30/8, mean age 61 y) who underwent pre-operative CT or MR imaging before surgery as well as transcriptome profiling were included in this IRB approved single centre retrospective study. Eleven qualitative and 4 quantitative imaging traits (size, enhancement ratios, wash-out ratio, tumour-to-liver contrast ratios)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…There is also active development of novel cancer biomarker assays, including assays for cancer‐specific DNA mutations, differentially methylated regions of DNA, microRNAs, long noncoding RNAs, native and posttranslationally modified proteins, and biochemical metabolites. Recent results suggest that there is differential expression of many biomolecules in exosomes released from tumor cells compared to those from normal cells …”
Section: Surveillancementioning
confidence: 99%
“…There is also active development of novel cancer biomarker assays, including assays for cancer‐specific DNA mutations, differentially methylated regions of DNA, microRNAs, long noncoding RNAs, native and posttranslationally modified proteins, and biochemical metabolites. Recent results suggest that there is differential expression of many biomolecules in exosomes released from tumor cells compared to those from normal cells …”
Section: Surveillancementioning
confidence: 99%
“…41 Some preliminary studies have revealed correlations between phenotypic imaging traits and genomic signatures in patients with HCC. 42,43 However, the small-sample size and limited imaging features may influence the reliability of the detected image-to-gene associations. Future studies could attempt to incorporate genomic characteristics into the radiomics model to capture more underlying behaviours in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…While similar to the prior study using CT, the pathologic identification of MVI may not correspond directly to a venous invasion genetic signature, and the results are not directly comparable. More recently, gene signatures of aggressive HCC phenotype were found to be associated with certain imaging traits in HCC imaged by contrast‐enhanced CT (26 patients) and MRI (12 patients), with an infiltrative pattern on imaging showing the highest number of positive associations . Interestingly, the authors did not find associations between enhancement ratios and gene expression signatures, but they propose the use of dynamic contrast‐enhanced (DCE)‐MRI for future prospective analyses given the limitation inherent to measurements of tumoral enhancement on arterial and portal venous phases alone.…”
Section: Livermentioning
confidence: 99%
“…More recently, gene signatures of aggressive HCC phenotype were found to be associated with certain imaging traits in HCC imaged by contrast-enhanced CT (26 patients) and MRI (12 patients), with an infiltrative pattern on imaging showing the highest number of positive associations. 39 Interestingly, the authors did not find associations between enhancement ratios and gene expression signatures, but they propose the use of dynamic contrast-enhanced (DCE)-MRI for future prospective analyses given the limitation inherent to measurements of tumoral enhancement on arterial and portal venous phases alone. Multiparametric MRI was later performed in a study of 14 patients with available HCC gene expression profiles at the same institution.…”
Section: Livermentioning
confidence: 99%